A Rare Case of Primary Malignant Mesenchymoma Arising from Submandibular Salivary Gland - Deshmukh, Abhay Vilas (Oman Med J, 2020)
Malignant mesenchymoma is a rare tumor in which there are two or more distinct mesenchymal components. These are generally considered as high-grade neoplasms and are usually associated with a poor prognosis. Here, we report a case of malignant mesenchymoma containing undifferentiated spindle cell sarcoma, leiomyosarcoma, chondrosarcoma, osteosarcoma, and areas with rhabdoid differentiation in a 54-year-old male. The primary tumor measured 5.5 × 4 × 3 cm and weighed 135 g arising from the left submandibular salivary gland. Fine-needle aspiration cytology showed the presence of pleomorphic spindle cell clusters with atypia and myxoid stroma. An impression of malignant salivary gland neoplasm was given. Diagnosis of malignant mesenchymoma was made on histopathological examination supported by immunohistochemistry showing strong positivity with p53, Ki-67, and focal positivity for smooth muscle actin, S-100, desmin, and negativity for cytokeratins. The exact histogenesis of malignant mesenchymoma and the optimal management strategy to decide the prognosis remains uncertain as it is a rare tumor.